2013
DOI: 10.1111/cbdd.12195
|View full text |Cite
|
Sign up to set email alerts
|

N‐substituted Piperazinopyridylsteroid Derivatives as Abiraterone Analogues Inhibit Growth and Induce Pro‐apoptosis in Human Hormone‐independent Prostate Cancer Cell Lines

Abstract: Nine new 17-(piperazin-1-yl)pyridin-5-yl)steroids as abiraterone analogues were synthesized. Compounds 5d and 5g showed selective activities against 17α-hydroxylase/C17,20-lyase (CYP17A1) and aromatase (CYP19), respectively. IC50 values of 5d were 5.09 and >50 μm, whereas these values for 5g were >50 μm and 7.40 μm, respectively, for CYP17A1 and CYP19. Molecular modelling highlighted that the inhibitor designed to bind cytochrome P450 haem iron is a necessary condition but not the only rationale to explain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
2
6
0
3
Order By: Relevance
“…It is interesting that abiraterone was markedly effective against PC3 tumors, which are AR‐negative, since its primary action is known to be blockade of androgen synthesis through inhibition of CYP17A1. However, several in vitro studies have demonstrated that the anti‐tumor effect of abiraterone in PC3 cells is not solely associated with blockade of androgen synthesis . Our in vivo studies would confirm these observations.…”
Section: Resultssupporting
confidence: 84%
“…It is interesting that abiraterone was markedly effective against PC3 tumors, which are AR‐negative, since its primary action is known to be blockade of androgen synthesis through inhibition of CYP17A1. However, several in vitro studies have demonstrated that the anti‐tumor effect of abiraterone in PC3 cells is not solely associated with blockade of androgen synthesis . Our in vivo studies would confirm these observations.…”
Section: Resultssupporting
confidence: 84%
“…The DU145 cells are an aggressive cell line derived from human prostate adenocarcinoma metastatic to the brain and are known to be sensitive to abiraterone. 37 These cells are androgen receptor-negative, but show significant expression of CYP17A1 both at the mRNA and protein levels. 38 The cytotoxic compound thapsigargin (TPG; 10 μM) was used as a positive control.…”
mentioning
confidence: 99%
“…5aSR -5a-редуктаза; 5b-редуктаза, 3b-HSD -3b-стероиддегидрогеназа. В работе [41] были синтезированы и исследованы производные абиратерона 20-28, содержащие объёмистые заместители в пиридиновом цикле (формула 3).…”
Section: производные и аналоги абиратерона и галетеронаunclassified
“…Молекулярный докинг показал, что связывание ингибитора 23 в активном центре CYP17A1 существенно отличалось от связывания абиратерона. Соединения 24, 26, 28 подавляли пролиферацию и стимулировали апоптоз только в гормон-независимых клетках карциномы простаты DU-145 и PC-3 [41].…”
Section: производные и аналоги абиратерона и галетеронаunclassified